Forum on Jerrold Levinson, "Contemplating Art" (Lebenswelt. Aesthetics and philosophy of experience., 2014)
Jerrold Levinson’s Contemplating Art provides the readers with a variety of heterogeneous topics and issues. The discussants who took part in the Forum about Levinson’s book chose four different “tracks” dealt with, offering four different reflections. The main topics of the debate are: music, historicity, aesthetic properties and aesthetic contextualism.Starting on the fact that music is one of the main fields of Contamplating Art Alessandro Bertinetto focus his paper on the ‘musical’ chapters of the book that 1) defend the theory of musical expressivity presented by Levinson in his previous books (the ‘theory of musical persona’); 2. articulate it in reference to particular aspects of musical experience, and 3. examine its contribution for the understanding of the narrative and dramatic dimension of music as well as 4., in general, for its artistic value. Michele Di Monte’s aim is to focus on the questions raised by the alleged essential historicality of the concept of art and the formal definition of the concept itself. He discusses, in particular, the epistemic basis and status of what Levinson calls ‘our present concept of art’, the logical outcomes of its role in defining and identifying the art of the past and the problematic relationship between a universality requirement and the theory’s pretension to historicality. Filippo Focosi discusses in the first place the passages of Levinson’s book where his paradigmatic aesthetic principle explicitly occurs; secondly, he shows how such a principle, as is there articulated, can disclose interest perspectives on other aspects of Levinson’s theories about art and aesthetic properties. The paper by Lisa Giombini focuses on on the role of context in Levinson’s definition of art.Afterdefining Levinson’s version of aesthetic contextualism, Giombiniunderlines how Levinson’s intentional-historical definition may provide fertile ground for a peculiar form of contextualism where the relevant context is constituted by the history of art and the practice of art alone. Finally she inquires whether Levinson’s identifying works of art with wholly relational intentionally-historically defined concepts may interfere with his adhesion to aesthetic realism.